Avant-garde After the Avant-garde in Croatian Poetry - Oblučar, Branislav (Poznańskie Studia Slawistyczne, 2020)
The article discusses the problem of the avant-garde in Croatian poetry during the second half of 20th century. It supports the thesis about the continuity of the avant-garde before and after World War II, and perceives the artistic and literary experiments of the neo and post-avant-garde as a part of a long avant-garde tradition. The analysis brings forward the different perceptions of avant-garde in the works of Radovan Ivšić and Josip Sever, and post-avant-garde poets of 1970s and 80s.